The effect of thyroidectomy on sexual cycle and pregnancy rates in rats - Risvanli, A; Aydin, M; Kaygusuzoglu, E; Timurkan, H (Scientific Technical Research Council Turkey, 2003)
We investigated the effect of hypothyroidism caused by thyroidectomy on the sexual cycle and pregnancy rates in rats. Twenty female rats were divided into two groups. The thyroid glands were totally extirpated in the first group (n = 10). An operation was performed but the thyroid glands were not extirpated in the second group (n = 10). In both groups, the differences in vaginal cytology were examined daily with vaginal irrigation, for 1 month starting 3 days after the operation. Preparations from the vaginal irrigation were stained with Giemsa. A male rat was placed in the cage containing the female rats during the estrous cycle for 12 h. The pregnancy of the rats was determined by following their parturation. In conclusion, it was observed that in thyroidectomized rats while the estrous number and pregnancy rates decreased, the length of the sexual cycle was extended.
Ratlarda tiroidektominin seksüel siklus ve gebe kalma oranlari üzerine etkisi
Keywords: thyroidectomy; sexual cycle; pregnancy; rat